Prostor a jeho obývání Zobrazení prostoru v díle Marie Noëlové, Suzanne Renaudové, Christiane Singerové a Sylvie Germainové - Bakešová, Václava (Cizí jazyky: jazykovědné a literárně vědné studie, 2019)
Title in English: Space and its habitation: A view of space in the works of Marie Noël, Suzanne Renaud, Christiane Singer and Sylvie Germain The publication summarizes the research results of various types of space in the literary works of four Christian inspired French authors, M. Noël, S. Renaud, C. Singer and S. Germain. Their literary texts cover the whole of the 20th century and show diversity in approaches to space, but also a difference in the literature of 1st and 2nd halves of 20th century. Methodologically, it proceeds from the phenomenological view of G. Bachelard on the intimate space of the home, through the open and sacred space according to M. Eliade's study, towards the geocritical analysis of the space, based on the almost unused B. Westphal's theory of geocriticism. The study of space shows that literature can not be separated from the outside world, on the contrary, it contributes to its better understanding.